Bacillus cereus in Raw Milk and its Virulence Genes - Abubaker, Hala S.; Abd El-kader, Shaimaa A.; Yassin, Shereen A. (Journal of Advanced Veterinary Research, 2023)
A frequent source of milk contamination is Bacillus cereus. The microorganism can contaminate raw milk at the time of milking since it is ubiquitous in the environment. In the current study, one hundred raw milk samples were obtained from farmers, supermarkets, street vendors and dairy shops in Egypt, collected samples were examined biochemically and by vietk 2 compact system to isolate Bacillus cereus. Prevalence values of B. cereus were 0, 20,8 and 12% respectively.Â The Mean Â± SE of the pH values for milk samples were 6.54 Â± 0.04, 6.48 Â± 0.06, 6.44 Â± 0.05 and 6.53 Â± 0.06 respectively, on the other hand sorchâ€™s test for milk samples was positive in a percentage of 12, 8, 40 and, 16, respectively. Molecular characterization of hlbA and ces showed positive reaction for 30 and 20% of samples. Growth, proteolytic and lipolytic activities of Bacillus cereus was 100, 100, 20 and 40, 40, 20 at 30â—¦C/48 h and 7Â°C/10 days, respectively. Outcomes of the in vitro testing for susceptibility indicated that the highest resistance to antibiotics was against macrolides and mono, B-lactamase, whereas moderate resistance was exhibited to gentamicin. The current study’s findings exhibited evidence of B. cereus isolation from raw milk has a high potential for producing food poisoning, so it is necessary to employ the techniques to lessen bacterial contamination while processing dairy products.